Nurturing Natural Beauty: Empowering MAN 1 Model Bengkulu's Female Students with Red Dragon Fruit (Hylocereus polyrhizus) Cosmetics Crafting Workshop - Masrijal, Camelia Dwi Putri; Taurina, Hilda; Lubis, Ashar Muda; Permasari, Rose Intan; Hermansyah, Oky; Slamet, Samwilson; Rahmawati, Suci; Rahmadhani, Aliyah; Monalisa, Shelyn Puteri; Wahid, Muhammad Ali Ashar (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: The use of lipstick, blush-on, and various colored cosmetic products is highly popular among teenage girls. However, the adverse effects of hazardous colorants in cosmetics include respiratory irritations, skin irritations, eye injuries, gastrointestinal toxicity, and carcinogenic properties. Red Dragon Fruit contains a significant amount of red anthocyanin antioxidants, making it a viable natural colorant for food, cosmetics, and textiles. This community engagement project aimed to enhance the understanding of teenage girls, especially students of MAN 1 Model City of Bengkulu, regarding illegal cosmetics containing harmful and prohibited ingredients. It also aimed to improve the girls' skills in crafting natural Lip Tint and Blush-On preparations from Red Dragon Fruit (Hylocereus Polyrhizus), promoting a return to nature in cosmetic choices. This initiative was expected to inspire creative ideas among teenagers for designing alternative economic activities centered on producing natural and halal cosmetics made from herbal ingredients. Methods: The project involved educational and awareness-raising activities about the dangers of forbidden cosmetic ingredients, followed by workshops on making Lip Tint and Blush-On formulations. These workshops were led by faculty members from the School of Medicine and the School of Pharmacy, with assistance from students of the Faculty of Mathematics and Natural Sciences at the University of Bengkulu. Results: Evaluation results showed that workshop participants experienced a 63.2% increased in knowledge and gained the ability to independently create Lip Tint and Blush-On products from red dragon fruit. Conclusion: The workshop successfully produced natural Lip Tint and Blush On and the project also heightened the students' interest in the Pharmacy Program.